A Biodegradable Hybrid Micro/Nano Conductive Zinc Paste for Paper‐Based Flexible Bioelectronics. Issue 10 (16th May 2022) - Zareei, Amin; Selvamani, Vidhya; Gopalakrishnan, Sarath; Kadian, Sachin; Maruthamuthu, Murali Kannan; He, Zihao; Nguyen, Juliane; Wang, Haiyan; Rahimi, Rahim
Abstract: Paper‐based electronics are emerging as a new class of technology with broad areas of application. Despite several efforts to fabricate new types of flexible electronic devices by screen printing of conductive paste, many of them are often nonbiodegradable, toxic, and expensive, limiting their practical use in bioresorbable paper‐based electronics. To address this need, a highly conductive and biodegradable bimodal conductive paste is developed using cost‐effective zinc‐based micro and nanoparticles with a facile low‐temperature sintering process compatible with paper substrates. The two‐step sintering process involves the removal of the insulating zinc oxide layer by spray coating acetic acid followed by a heat press sintering process to ensure the formation of highly packed and continuous metallic traces. The required conditions for the heat press sintering process are systematically studied using electrical, optical, and mechanical characterization techniques. The results of these investigations revealed an ultra‐packed microstructure with high electrical conductivity (0.5 × 10 5 S m −1 ) and low oxide content that is obtained with a heat press sintering setting of 220 °C for 60 s. Finally, as a proof of concept, the conductive paste with an optimized sintering process is used to fabricate a wearable wireless heater for remote‐controlled release of therapeutics. The controlled delivery of the system is validated in the practical and on‐demand delivery of antibiotics for eradicating commonly found bacteria such as Staphylococcus aureus in dermal wound infections. The biocompatibility of all the materials and manufacturing process is validated by NIH/3T3 fibroblast cells via MTT assay and live/dead staining. Abstract : In this work, a novel highly conductive and biodegradable bimodal paste is developed for flexible paper‐based bioelectronics. The paste is composed of Zn micro/nano particles and can be sintered with a low‐temperature sintering process that involves spray coating acetic acid to remove ZnO layer followed by heat press sintering to ensure formation of highly packed and continuous metallic traces.